Redesigning the retention strategy against the emerging turnover of generation y: Revisiting the long-standing problems from 20th to 21st century - Hassan M.; Jambulingam M.; Alam M.N.; Islam S. (Allied Business Academies, 2023)
Although many investigations carried out on employee turnover more than one century, still investigations and reviews reveal that the problem of turnover remains unresolved and increasing within Generation Y employee. Excessive turnover counts great loss to any organization of the world. This comprehensive study included from the birth of turnover research up to till date. Also, by this approach, authors find the necessities of conceptualizing the integrated employee retention strategies, problems and gaps of failures. It is observed that at present the young employees from Generation Y (Millennial) are not contented with their profession and have a tendency of leaving the job with and without valid reasons. Most of the employees from Generation Y directly or indirectly opted for voluntary resignation for better opportunities or self-employment. It is also found that there are essences of frustration about Generation Y from employees and employers perspectives. Considering the demoted images, some communities even trying to change their retention approaches whereas merely, these types of in general efforts cannot be a solution against these prospective and forthcoming major stakeholders for future workplaces. This review of literature and qualitative investigation conceptualize the significant events of the former and ongoing century related to the turnover of employees. More specifically, this investigation stress on different generational cohorts and recent observations which merge simultaneously with concurrent investigations on Generation Y through an integrated approach. Most of the study on turnover was carried out on western context and perspectives, whereas turnover problems exist all over the world. Another remarkable factor was the rate of turnover is significant in private sector than public sectors; whereas the private sector got significant stakes for the development of any country. Every organization got earnest desires to get the best output and lesser turnover to avoid brain drain, to save excessive turnover costs, and to retain experience staffs. It has become very much important for any organization to keep constant productivity and output through retention. It is found that employees who are satisfied with their job have better retention, companionship with fellow staff members, and produce a higher quality of work. Earlier concentration was given only towards the fulfilment of intrinsic and extrinsic motivational factors as a part of Job satisfaction of employee. Whereas through this investigation it is found that besides motivational approaches there are necessities to formulate retention friendly strategies which include servant leadership, management initiative, soft HRM, work life balance, ethical climates. To fulfil target group practical requirements, these viable requirements are the vital instruments for Generation Y retention, which required to be integrated as strategic solutions. This guidance for practical users and academic researchers became essential to fight against the global storms of Generation Y turnover to combat overt and covert losses due to frequent turnover. 2019, Allied Business Academies. All rights reserved.